Integrating Islamic Religious Education in Developing an Islamic Economics Curriculum to Support SDG 1 on Poverty Alleviation - Hilmin; Dwi Noviani; Mohammad Faizal; Abdulhafiz Hile; Meriyati (Profetika: Jurnal Studi Islam, 2024)
Objective: This study aims to analyze the integration of Islamic Religious Education in the development of the Islamic Economics curriculum at the Al-Qur’an Al-Ittifaqiah Islamic Religious Institute (IAIQI) Indralaya, Indonesia, as a strategic effort to support SDG 1 on poverty alleviation. Theoretical framework: Theoretically, this study is grounded in problem-based learning (PBL) and the integration of values-based education, which together provide a framework for cultivating not only cognitive competence but also ethical awareness in economic behavior. Literature review: A review of the existing literature reveals a growing concern regarding the mismatch between Islamic Economics education and real-world economic disparities. Previous studies emphasize the importance of aligning curriculum content with contemporary issues such as economic inequality, unemployment, and community empowerment. Methods: Methodologically, this research employs a qualitative case study approach through document analysis, curriculum review, and semi-structured interviews with faculty members, curriculum developers, and policy stakeholders. Results: The findings indicate that effective curriculum development must incorporate real-life community problems, ethical reasoning, and interdisciplinary knowledge. The inclusion of Islamic Religious Education enhances the moral dimension of economic decision-making and contributes to shaping students as agents of socioeconomic transformation. Furthermore, collaboration between universities, local governments, and community institutions emerged as a critical factor in ensuring the curriculum's relevance and impact. Implications: The implications of this study underscore the urgency of transforming Islamic Economics education into a practical tool for achieving social justice and economic empowerment, in line with the Sustainable Development Goals. Novelty: The novelty of this research lies in proposing an integrative curriculum model that explicitly links Islamic values, educational theory, and SDG 1, positioning religious education as a catalyst for meaningful poverty alleviation.